PELAKSANAAN TERAPI PERILAKU BAGI ANAK PENYANDANG AUTIS DI SEKOLAH LUAR BIASA (SLB) KUSUMA BANGSA KOTA KENDARI - Santri Tri Putri; Syaifudin Suhri Kasim; Darmin Tuwu (Universitas Halu Oleo, 2023)
This study aims to form students with physical and mental disorders, behavioral disorders and social disorders so that they are able to develop attitudes, knowledge and skills as individuals and members of the community in social interaction to develop their basic potentials optimally. The results showed that in achieving changes in children with autism at the Kusuma Bangsa Special School (SLB) in Kendari City, several stages were needed including conducting assessments, setting goals (goal setting), technical implementation and evaluation. In conducting an assessment of children with autism, the therapy teacher found several problems with each child, such as being difficult to manage, not wanting to be quiet, not wanting to listen, not being able to sit quietly, often hitting, etc. Then after the child's problems are known, the therapy teacher provides behavioral therapy which will then be evaluated through a special assessment. Then determine the goals of therapy that will be given to children in the form of behavior therapy that can help children with autism behave well. To achieve good behavior towards children, the type of therapy given is not only behavior therapy but other types of therapy such as play therapy, physical therapy, social therapy and developmental therapy. To achieve the desired behavior change, several behavioral therapy techniques are given to autistic children during therapy, such as characterization modeling. In this technique, children are instructed to follow things that are done by a teacher implementing therapy, such as following how to chat well. By bellowing, children can train their fine motor skills. positive reinforcement, this technique is used to encourage autistic children to be able to take part in therapy well, such as when a child succeeds in doing therapy and following the instructions properly from the teacher implementing therapy, the child will be given a reward in the form of praise in the form of gifts and deletion, deletion techniques are carried out aims to eliminate the behavior of autistic children and the teacher implementing therapy will teach good behavior according to their age which is more independent. Then evaluate, that the Kusuma Bangsa Special School (SLB) in Kendari City is very active and regular in providing therapy to children with autism. With therapy children can experience good behavior changes while at school. Some therapies are able to improve children's abilities to be even better so that children are used to the therapy they receive from the Kusuma Bangsa Special School (SLB), Kendari City.